Test method for removal rate of trichloroethylene in waste asphalt mixture recycled coarse aggregate

CN122961841APending Publication Date: 2026-10-23GUANGDONG HUALU TRANSPORTATION TECHNOLOGY CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611384106.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0007]本发明的目的是提供一种废旧沥青混合料回收粗集料中三氯乙烯清除率的测试方法,以解决现有技术中未提出废旧沥青混合料抽提法得到的粗集料中三氯乙烯清除效果定量化测试方法的问题

Benefits of technology

(1)本发明通过引入公式1计算三氯乙烯的清除率,定量表征三氯乙烯的清除程度,克服了现有技术中仅仅依靠肉眼观察气泡或简单烘干称重无法精准判断三氯乙烯残留量的缺陷,使得试验结果更加准确。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122961841A_ABST
    Figure CN122961841A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of material testing, and particularly relates to a method for testing the removal rate of trichloroethylene in waste asphalt mixture recycled coarse aggregate, comprising the following steps: taking two coarse aggregate samples with equal mass from coarse aggregate obtained by extraction method, and recording the mass of the coarse aggregate sample as m1; placing one of the coarse aggregate samples into a combustion furnace for sufficient combustion, then weighing the mass of the coarse aggregate again and recording it as m2; washing and heating and drying the other coarse aggregate sample, then weighing the mass of the coarse aggregate again and recording it as m3; and calculating the removal rate of trichloroethylene according to formula 1. Comparing the calculated removal rate with the preset technical requirements to determine the subsequent experimental method. The present application provides a standardized operation process, quantitatively evaluates the removal of trichloroethylene in coarse aggregate, and directly determines whether downstream testing can be performed according to the removal, thereby ensuring the accuracy of subsequent testing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials testing technology, and in particular relates to a test method for the removal rate of trichloroethylene in coarse aggregates recycled from waste asphalt mixtures. Background Technology

[0002] Asphalt pavement is the most common pavement structure for modern highways and urban roads. However, with increasing service life, asphalt pavements gradually develop problems such as cracks, ruts, and loosening under the long-term effects of vehicle loads and the natural environment, requiring regular maintenance. This process generates a large amount of reclaimed asphalt pavement (RAP). To comprehensively utilize this reclaimed asphalt pavement, it is recycled, crushed, and screened, then remixed with new aggregates, new asphalt, and recycling agents in a specific ratio to form recycled asphalt pavement for road construction. This not only saves sand and gravel resources and petroleum asphalt, reducing costs, but also reduces waste accumulation. However, compared to virgin asphalt pavement, the mix design of recycled asphalt pavement is more complex. The key is that RAP is a composite material tightly bound together with aged asphalt and old aggregates. Before design, the asphalt and aggregates must be separated using an extraction method to separately determine the properties of the old asphalt and the gradation and density parameters of the old aggregates. In the extraction method, trichloroethylene is usually used as a solvent to dissolve the asphalt in the RAP. Then, the old aggregate is obtained by centrifugation or filtration. Subsequently, the old aggregate needs to be screened to determine the particle size distribution and its density is determined by the basket method. These data are the basis for determining the gradation design, theoretical maximum relative density and optimal asphalt-aggregate ratio of the recycled asphalt mixture.

[0003] In practice, trichloroethylene (TCE) exhibits strong permeability and surface adsorption properties, especially in porous aggregates with rough surfaces and numerous internal pores. TCE easily penetrates and remains within the pores of the aggregate. According to the current "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG 3410-2025), after extraction, the old aggregate is typically dried in an oven at 105℃±5℃ to constant weight, attempting to remove TCE through heat volatilization. However, practice has shown that this method is time-consuming, often requiring several hours or even longer, and cannot effectively remove TCE deeply embedded within the pores. When using the basket method to test the density of old aggregates containing TCE, after immersion in water, the TCE slowly escapes from the pores, forming numerous air bubbles on the aggregate surface. These bubbles alter the buoyancy of the aggregate in water, leading to a lower measured mass in water and consequently, a lower calculated density. Distortion in the density of old aggregates can affect the entire mix design process of recycled asphalt mixtures. The theoretical maximum relative density may be underestimated due to incorrect aggregate density input, leading to inaccurate calculations of volumetric parameters such as porosity and aggregate void ratio. This results in insufficient asphalt usage during actual construction, directly reducing the fatigue cracking resistance and water stability of recycled pavements, severely impacting their durability. Furthermore, residual trichloroethylene can interfere with the evaluation of aggregate-asphalt adhesion. In adhesion tests, residual solvents may dissolve or soften the asphalt film, causing an underestimation of the adhesion grade and thus incorrectly determining that the aggregate-asphalt compatibility is unqualified.

[0004] To remove trichloroethylene from old aggregates, existing technologies mostly employ washing methods. Chinese invention patent application CN104215549A discloses a density testing method for recovering aggregates from asphalt pavement materials. This method involves sieving and classifying the aggregates obtained by extraction, washing coarse and fine aggregates with an anionic surfactant aqueous solution until all surface air bubbles are removed and no foam floats on the water surface, and then drying them before using the basket method to obtain the apparent relative density and bulk relative density. This technical solution utilizes anionic surfactant aqueous solution to thoroughly wash away residual trichloroethylene from the aggregates, improving the accuracy of aggregate density measurement. Chinese invention patent application CN115078175A discloses a method for testing the density of RAP aggregates after extraction. Under negative pressure, the RAP aggregates undergo primary treatment with an ethanol solvent to allow the ethanol solvent to fuse with the trichloroethylene on the surface of the RAP aggregates. Under ultrasonic conditions, the primary-treated RAP aggregates undergo at least one secondary treatment with an ethanol solvent to dissolve the trichloroethylene on the surface of the RAP aggregates. The RAP aggregates after secondary treatment are then dried, and their density is tested. This technical solution combines negative pressure and ultrasound to achieve efficient cleaning of RAP aggregates and ensure accurate testing of their density.

[0005] While the aforementioned technical solutions employ chemical cleaning or a combination of negative pressure and ultrasonic cleaning in the presence of ethanol to remove trichloroethylene from old aggregates, their removal effectiveness is primarily assessed qualitatively by observing physical phenomena such as bubbles and foam, or relies on the inherent efficiency of the process itself. This assessment of removal effectiveness is merely a vague, empirical judgment. Quantifying the removal effect of trichloroethylene from old aggregates is crucial for guiding the mix design of recycled asphalt mixtures.

[0006] Therefore, there is an urgent need for a rapid and accurate method to quantitatively determine the degree of trichloroethylene removal in coarse aggregates, so as to clarify whether the aggregates can be used for downstream testing such as density testing and adhesion testing. Summary of the Invention

[0007] The purpose of this invention is to provide a test method for the removal rate of trichloroethylene in coarse aggregates recovered from waste asphalt mixtures, so as to solve the problem that the prior art does not provide a quantitative test method for the removal effect of trichloroethylene in coarse aggregates obtained by the extraction method of waste asphalt mixtures.

[0008] To achieve the above objectives, this invention provides a method for testing the trichloroethylene removal rate in recycled coarse aggregates from waste asphalt mixtures, comprising the following steps: S1: Test preparation: Weigh two coarse aggregate samples of equal mass from the coarse aggregate obtained by the extraction method. Record the mass of the coarse aggregate sample as m1. S2: Determination of reference sample: After one coarse aggregate sample is fully burned in the combustion furnace, the mass of the coarse aggregate sample is weighed again and recorded as m2; S3: Trichloroethylene removal treatment: After washing and drying another coarse aggregate sample, weigh the coarse aggregate sample again and record the mass as m3; S4: Removal rate calculation: Calculate the removal rate of trichloroethylene according to Formula 1. Formula 1, In the formula, λ represents the trichloroethylene removal rate.

[0009] Furthermore, in step S1, the mass of the coarse aggregate sample weighed shall not be less than 1.5 kg.

[0010] Furthermore, in step S2, the temperature of the combustion furnace is 475-490℃, and the combustion time is 30-45 minutes.

[0011] In order to ensure that trichloroethylene in the reference sample is completely removed, the present invention preferably uses the above-mentioned combustion temperature and combustion time to remove trichloroethylene in the small pores of the coarse aggregate by high temperature until the mass of the coarse aggregate sample no longer changes under the above combustion conditions, indicating that the reference sample has been prepared and its mass can be recorded as m2.

[0012] Furthermore, the specific process of washing in step S3 involves stirring and cleaning with an aqueous solution of laundry detergent or liquid.

[0013] Furthermore, the specific process of heating and drying in step S3 is to heat at 90-110℃ for 5-10 hours.

[0014] To ensure effective removal of trichloroethylene from coarse aggregate samples, this invention employs the aforementioned washing and heating / drying parameters to perform the trichloroethylene removal process until the mass of the coarse aggregate sample no longer changes after heating and drying. At this point, the trichloroethylene in the coarse aggregate sample is essentially completely removed. To further quantitatively characterize the trichloroethylene removal effect, calculations are performed using the corresponding formula. By comparing these calculations with technical requirements, the subsequent testing process for the coarse aggregate is directly guided, thereby ensuring that the recycled asphalt mixture after mix design possesses excellent comprehensive performance.

[0015] This invention provides a method for recycling coarse aggregates, comprising the following steps: (1) The recycled coarse aggregate obtained by the extraction method from the waste asphalt mixture is washed and heated and dried to obtain pretreated material; (2) The trichloroethylene removal rate of the pretreated material was tested according to the above test method; The trichloroethylene removal rate was calculated according to Formula 1. Formula 1, In the formula, λ is the trichloroethylene removal rate; (3) When λ≥95%, the pretreated material is used for downstream testing, including density testing, water absorption testing, adhesion testing and strength testing. When λ<95%, the pretreated material is washed and heated and dried again.

[0016] Preferably, a reference sample with a mass of m1 is reserved from the recycled coarse aggregate obtained by extraction of waste asphalt mixture, and the remaining recycled coarse aggregate with a mass of m4 is washed and dried to obtain pretreated material with a mass of m5; after the reference sample is fully burned, a mass of m2 is obtained. The mass (m3) of the recovered coarse aggregate, which is the same mass as the reference sample, after washing and heating-drying treatment is calculated according to the following formula: Formula 2; Substituting m1, m2, and m3 into Formula 1, the trichloroethylene removal rate of the pretreated material is calculated.

[0017] In this invention, when the trichloroethylene removal rate is greater than or equal to 95%, most of the trichloroethylene in the coarse aggregate sample is washed away, and the coarse aggregate can basically undergo all downstream tests. At this point, density testing, which is highly sensitive to trichloroethylene residue, can guarantee its accuracy. However, when the trichloroethylene removal rate is greater than or equal to 50% but less than 95%, some downstream tests sensitive to trichloroethylene residue cannot guarantee the accuracy of their data; for example, density and water absorption tests cannot be performed. Some tests relatively insensitive to trichloroethylene residue, such as adhesion and soundness tests, can still be performed with guaranteed accuracy. The various downstream tests of the coarse aggregate in this invention can be conducted according to the "Test Procedures for Aggregates in Highway Engineering JTG E42-2005". To ensure more accurate data results for all tests, the calculated trichloroethylene removal rate needs to be greater than or equal to 95%.

[0018] The present invention, by adopting the above-described technical solution, has at least the following beneficial effects compared with the prior art: (1) The present invention calculates the removal rate of trichloroethylene by introducing Formula 1, quantitatively characterizes the degree of removal of trichloroethylene, and overcomes the defect of the prior art that cannot accurately determine the residual amount of trichloroethylene by simply observing bubbles with the naked eye or by drying and weighing, so that the test results are more accurate.

[0019] (2) The present invention sets a threshold in the processing method of recycled coarse aggregates to avoid data errors caused by residue interference, and significantly improves the reliability of coarse aggregate reuse.

[0020] (3) The present invention provides a complete, specific and quantifiable set of operating procedures from sample preparation, reference sample determination, cleaning treatment to result evaluation. The data obtained by different operators and different laboratories have good repeatability and comparability, which is convenient for application in the mix design of recycled asphalt mixtures.

[0021] (4) The present invention uses detergent cleaning combined with continuous heating and drying, and is supplemented by quantitative judgment indicators, which can quickly determine whether the required removal rate has been achieved, avoid unnecessary repeated drying, and improve the overall experimental efficiency. Attached Figure Description

[0022] Figure 1 This is a schematic diagram of the process flow of the present invention. Detailed Implementation

[0023] Example 1 This embodiment studies the density change of coarse aggregate under different trichloroethylene removal rates. The specific steps are as follows: S1: Take the coarse aggregate obtained by the extraction method. The extraction method is carried out in accordance with the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG 3410-2025) (T 0722-2025) to obtain coarse aggregate samples of 10~20mm and 5~10mm. The coarse aggregate samples of these two particle size ranges are processed as follows.

[0024] Weigh five equal portions of coarse aggregate samples and record the mass of each sample as m1. The specific mass of each coarse aggregate sample is 2000.0g.

[0025] S2: Take the first coarse aggregate sample and put it into the combustion furnace. After burning it for 40 minutes at 482±5℃, the difference between the two weighings should not exceed 0.1g. At this time, the mass of the coarse aggregate sample no longer changes. Weigh the mass of the coarse aggregate sample at this time and record it as m2.

[0026] S3: Take the second, third, fourth and fifth coarse aggregate samples and perform four different washing and heating drying processes. After completing the above four processes, weigh the mass of the coarse aggregate samples at this time and record it as m3.

[0027] S4: Substitute the four m3 values ​​measured in step S3 into Formula 1 to calculate the trichloroethylene removal rate; Formula 1, In the formula, λ represents the trichloroethylene removal rate.

[0028] The final calculations showed that the removal rates for the four treatment processes were 20%, 60%, 95%, and 98%, respectively.

[0029] The coarse aggregate sample with a removal rate of 20% was not subjected to the corresponding washing and heating drying process; The coarse aggregate sample with a removal rate of 60% was washed with ordinary water. The coarse aggregate sample was completely immersed in water and stirred at 120 r / min for 30 min. After washing, it was heated at 100℃ for 6 h. At this time, the difference between the two weighings did not exceed 0.1 g, and the mass of the coarse aggregate sample no longer changed. The coarse aggregate sample with a removal rate of 95% was washed with laundry detergent. The laundry detergent was prepared into an appropriate aqueous solution, and the coarse aggregate sample was completely immersed in the 0.3wt% laundry detergent aqueous solution. The solution was stirred at 120r / min for 45min. After washing, the sample was repeatedly stirred and rinsed in water until no more bubbles were generated. The laundry detergent was removed, and the sample was then heated at 100℃ for 7h. At this point, the difference between the two weighings did not exceed 0.1g, and the mass of the coarse aggregate no longer changed.

[0030] The coarse aggregate sample with a removal rate of 98% was washed with laundry detergent. The laundry detergent was prepared into an appropriate aqueous solution, and the coarse aggregate sample was completely immersed in the 0.3wt% laundry detergent aqueous solution. The solution was stirred at 120r / min for 60min. After washing, the sample was repeatedly stirred and rinsed in water until no more bubbles were generated. The laundry detergent was removed, and the sample was then heated at 100℃ for 8h. At this point, the difference between the two weighings did not exceed 0.1g, and the mass of the coarse aggregate no longer changed.

[0031] The four coarse aggregate samples, after washing and heating and drying, were subjected to density tests using the basket method (《Test Procedure for Aggregates in Highway Engineering JTG E42-2005》(T0304)) to obtain the apparent relative density values ​​of the coarse aggregate when the trichloroethylene removal rates were 20%, 60%, 95%, and 98%, respectively. The test results are shown in Table 1.

[0032] Table 1. Test results of coarse aggregate density at different trichloroethylene removal rates

[0033] As shown in Table 1, the trichloroethylene removal rate has a significant impact on the density test of aggregates. With the increase of the trichloroethylene removal rate, the apparent relative density of coarse aggregates increases. When the removal rate reaches 95% and 98%, the density value hardly changes, indicating that the residual amount of trichloroethylene has almost negligible influence on the density test. When the removal rate is 20% and 60%, the density value is significantly lower, indicating that the residual trichloroethylene in the coarse aggregates will still escape and form bubbles after immersion in water, interfering with buoyancy measurement and thus leading to a lower density value. Therefore, when the trichloroethylene removal rate is ≥95%, the trichloroethylene removal rate has little impact on the density test results of coarse aggregates. The density test is very sensitive to residual trichloroethylene, and the test results are more accurate when the removal rate is above 95%.

[0034] Example 2 This embodiment studies the performance of recycled asphalt mixtures obtained by applying coarse aggregates with different trichloroethylene removal rates in Example 1 to the mix design of recycled asphalt mixture AC-13. The preparation process of recycled asphalt mixtures involves mixing waste asphalt mixtures, new asphalt, and new aggregates. Asphalt mixture samples were prepared according to method T0702 of the "Test Specifications for Asphalt and Asphalt Mixtures in Highway Engineering JTG 3410-2025", and the mix design was carried out according to the mix design method of the "Technical Specifications for Construction of Asphalt Pavement on Highways JTGF40-2004". The results show that the trichloroethylene removal rate of the coarse aggregates has a significant impact on the downstream test data, thus affecting the performance of the recycled asphalt mixtures. Table 2 shows the test results of recycled asphalt mixtures prepared with coarse aggregates with different trichloroethylene removal rates. The theoretical maximum density was determined according to test method T0711 of the "Test Specifications for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG3410-2025).

[0035] Table 2. AC-13 mix design results for recycled asphalt mixtures

[0036] Table 2 shows that the higher the trichloroethylene removal rate of the coarse aggregate, the greater the theoretical maximum density, indicating that the measured density of the aggregate is closer to the true value. Furthermore, when the removal rate increases from 60% to 95%, the asphalt-aggregate ratio increases from 4.8% to 4.9%, and the asphalt-aggregate ratio of the recycled asphalt mixture can increase by 0.1 percentage points. This indicates that a more accurate aggregate density leads to a higher asphalt content design, which can improve the durability of the recycled asphalt mixture. If aggregates with insufficient removal rates are used in mix design, it will result in insufficient asphalt content, affecting the crack resistance and water stability of the recycled asphalt mixture. To ensure the rationality of the recycled asphalt mixture design, the trichloroethylene removal rate of the coarse aggregate should be ≥95%.

[0037] Example 3 This embodiment studies the changes in the adhesiveness of coarse aggregates with different trichloroethylene removal rates. The specific steps are as follows: S1: Take the coarse aggregate obtained by the extraction method. The extraction method is carried out in accordance with the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG 3410-2025) (T 0722-2025). Two types of coarse aggregate samples were obtained, namely granite and diabase. The following treatments were performed on the two types of coarse aggregate samples respectively.

[0038] Weigh four coarse aggregate samples of equal mass and record the mass of each sample as m1. The specific mass of each coarse aggregate sample is 2000.0g.

[0039] S2: Take the first coarse aggregate sample and put it into the combustion furnace. After burning it for 45 minutes at 482±5℃, remove the trichloroethylene. At this time, the difference between the two weighings does not exceed 0.1g, and the mass of the coarse aggregate sample no longer changes. Weigh the mass of the coarse aggregate sample at this time and record it as m2.

[0040] S3: Take the second, third and fourth coarse aggregate samples and perform three washing and drying processes respectively. After completing the above three processes, weigh the mass of the coarse aggregate samples at this time and record it as m3.

[0041] S4: Substitute the m3 measured by the three treatment processes in step S3 into Formula 1 to calculate the trichloroethylene removal rate. Formula 1, In the formula, λ represents the trichloroethylene removal rate.

[0042] The final removal rates for the three treatment processes were calculated to be 30%, 55%, and 95%, respectively.

[0043] The coarse aggregate sample with a removal rate of 30% was not subjected to the corresponding washing and heating drying process; The coarse aggregate sample with a removal rate of 55% was washed with ordinary water. The coarse aggregate sample was completely immersed in water and stirred at 120 r / min for 30 min. After washing, it was heated at 100℃ for 5 h. At this time, the difference between the two weighings did not exceed 0.1 g, and the mass of the coarse aggregate sample no longer changed. The coarse aggregate sample with a removal rate of 95% was washed with laundry detergent. The laundry detergent was prepared into an appropriate aqueous solution. The coarse aggregate sample was placed in the 0.3wt% laundry detergent aqueous solution and stirred at 120r / min for 50min. After washing, it was repeatedly stirred and washed in water until no more bubbles were generated. The laundry detergent was removed, and then it was heated at 100℃ for 8h. At this time, the difference between the two weighings did not exceed 0.1g, and the mass of the coarse aggregate no longer changed.

[0044] The three coarse aggregate samples, after washing and heat drying, were subjected to adhesion tests according to Test Method T0616 of the "Test Procedures for Highway Asphalt and Asphalt Mixtures" (JTG 3410-2025). The adhesion results between the coarse aggregate samples and asphalt were obtained when the trichloroethylene removal rates of the coarse aggregate were 30%, 55%, and 99%, respectively. The asphalt included modified asphalt and ordinary asphalt. The modified asphalt was SBS modified asphalt, Shell brand, PG76 grade, and the ordinary asphalt was ordinary base asphalt, Shell brand, 70# asphalt. The test results are shown in Table 3.

[0045] Table 3. Adhesion test results of coarse aggregate and asphalt with different trichloroethylene removal rates.

[0046] Table 3 shows that the trichloroethylene removal rate affects the adhesion between coarse aggregate and asphalt, especially for ordinary asphalt. When the trichloroethylene removal rate is below 55%, the adhesion grade between granite and ordinary asphalt is only level 3, and the adhesion grade between granite and diabase is only level 4. When the trichloroethylene removal rate reaches 99%, the adhesion grade between granite and diabase can reach level 4, and the adhesion grade between granite and diabase can reach level 5. This demonstrates that the trichloroethylene removal rate has a significant impact on the adhesion between asphalt and aggregate. Table 3 also shows that, compared to ordinary asphalt, modified asphalt is less sensitive to the residual amount of trichloroethylene in coarse aggregate. Even at a removal rate of 30%, the adhesion grade of modified asphalt is still relatively high, with granite at level 4 and diabase at level 5, indicating that the modified asphalt film has good resistance to residual solvents. Therefore, for ordinary asphalt or aggregates with poor adhesion, a trichloroethylene removal rate ≥95% yields more accurate viscosity test results. For SBS modified asphalt, an removal rate between 50% and 95% still allows for adhesion testing while maintaining accuracy. To ensure the accuracy of adhesion testing, the trichloroethylene removal rate should be ≥95%. Under this condition, the adhesion test results for both modified and ordinary asphalt are relatively accurate.

[0047] Example 4 This embodiment uses coarse aggregate (particle size > 4.75 mm) extracted from a certain AC-16 asphalt mixture as an example to verify the test method of the present invention.

[0048] like Figure 1 As shown, this embodiment provides a method for recycling coarse aggregates, including the following steps: (1) The recycled coarse aggregate obtained by extraction of waste asphalt mixture is aired in a ventilated indoor place for 40 minutes. Then, a small number of reference samples are reserved. Then, a large amount of the remaining recycled coarse aggregate is washed and heated to dry to obtain pretreated material. The washing and heating drying process is as follows: the washing liquid is prepared into a corresponding washing liquid aqueous solution, the remaining recycled coarse aggregate is placed in a 0.3wt% washing liquid aqueous solution, stirred at 120r / min for 30min, and after washing, it is repeatedly stirred and washed in water until no more bubbles are generated. The washing liquid is removed, and then heated at 100℃ for 6h to obtain pretreated material. The mass of the reference sample is m1, m1 = 2000.0 g. The reference sample is placed in a combustion furnace at 482±5℃ and burned for 45 min. When the difference between the two weighings does not exceed 0.1 g, the trichloroethylene is completely removed. The mass of the reference sample is weighed again, m2 = 1985.5 g. The mass of the remaining recovered coarse aggregate is m4, m4 = 10000.0 g, and the mass of the pretreated material is m5, m5 = 9936.0 g. (2) Calculate the mass m3 of the recovered coarse aggregate, which is the same mass as the reference sample, after washing and heating drying. The calculation formula is as follows: Formula 2; After calculation, m3 = 1987.2g; (3) Calculate the trichloroethylene removal rate according to Formula 1. Formula 1, In the formula, λ represents the trichloroethylene removal rate.

[0049] (4) Result determination: λ<95%, the above pretreated material is unqualified and needs to be washed and dried again. If the coarse aggregate is used directly for adhesion test without being washed and dried again, the results are as follows: the adhesion grade with ordinary asphalt is level 4, and the grade with modified asphalt is level 5. Since the type of coarse aggregate and the type of asphalt will affect the accuracy of the test results, according to the test results of Example 3, the above pretreated material should be subjected to trichloroethylene removal process again to ensure the accuracy of all downstream tests.

[0050] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the technical solutions of the present invention, and these modifications or equivalent substitutions cannot cause the modified technical solutions to deviate from the spirit and scope of the technical solutions of the present invention.

Claims

1. A method for testing the trichloroethylene removal rate in recycled coarse aggregates from waste asphalt mixtures, characterized in that: Includes the following steps: S1: Test preparation: Weigh two coarse aggregate samples of equal mass from the coarse aggregate obtained by the extraction method. Record the mass of the coarse aggregate sample as m1. S2: Determination of reference sample: After one coarse aggregate sample is fully burned in the combustion furnace, the mass of the coarse aggregate sample is weighed again and recorded as m2; S3: Trichloroethylene removal treatment: After washing and drying another coarse aggregate sample, weigh the coarse aggregate sample again and record the mass as m3; S4: Removal rate calculation: Calculate the removal rate of trichloroethylene according to Formula 1. Official 1, In the formula, λ represents the trichloroethylene removal rate.

2. The method for testing the trichloroethylene removal rate in recycled coarse aggregates of waste asphalt mixtures according to claim 1, characterized in that: In step S1, the mass of the coarse aggregate sample weighed shall not be less than 1.5 kg.

3. The method for testing the trichloroethylene removal rate in recycled coarse aggregates of waste asphalt mixtures according to claim 1, characterized in that: In step S2, the temperature of the combustion furnace is 475-490℃, and the combustion time is 30-45 minutes.

4. The method for testing the trichloroethylene removal rate in recycled coarse aggregates of waste asphalt mixtures according to claim 1, characterized in that: The specific process of washing in step S3 is to use an aqueous solution of laundry detergent or liquid to stir and clean.

5. The method for testing the trichloroethylene removal rate in recycled coarse aggregates of waste asphalt mixtures according to claim 1, characterized in that: The specific process of heating and drying in step S3 is to heat at 90-110℃ for 5-10 hours.

6. A method for processing recycled coarse aggregates, characterized in that, Includes the following steps: (1) The recycled coarse aggregate obtained by the extraction method of waste asphalt mixture is washed and heated and dried to obtain pretreated material; (2) The trichloroethylene removal rate of the pretreated material is tested according to the test method described in any one of claims 1 to 5; The trichloroethylene removal rate was calculated according to Formula 1. Official 1, In the formula, λ is the trichloroethylene removal rate; (3) When λ≥95%, the pretreated material is used for downstream testing, including density testing, water absorption testing, adhesion testing and strength testing. When λ<95%, the pretreated material is washed and heated and dried again.

7. The method for processing recycled coarse aggregate according to claim 6, characterized in that: A reference sample with a mass of m1 is reserved from the recycled coarse aggregate obtained by extraction of waste asphalt mixture, and the remaining recycled coarse aggregate with a mass of m4 is washed and dried to obtain pretreated material with a mass of m5. The mass m2 was obtained after the reference sample was fully burned; The mass (m3) of the recovered coarse aggregate, which is the same mass as the reference sample, after washing and heating-drying treatment is calculated according to the following formula: Official 2; Substituting m1, m2, and m3 into Formula 1, the trichloroethylene removal rate of the pretreated material is calculated.

8. The method for processing recycled coarse aggregate according to claim 7, characterized in that: The mass of the reserved reference sample shall not be less than 1.5 kg.

9. The method for processing recycled coarse aggregate according to claim 7, characterized in that: The reference sample was burned in a combustion furnace at 475-490℃ for 30-45 minutes.

Citation Information

Patent Citations

  • Density testing method of mineral aggregate in recycled asphalt pavement material

    CN104215549A

  • Method for testing density of aggregate after extraction of asphalt recovery old material

    CN115078175A